REFLEKSI PENDIDIKAN MULTIKULTURAL PADA PEMUJAAN HINDU-ISLAM DI PURA KRAMAT DESA ADAT SESEH KECAMATAN MENGWI KABUPATEN BADUNG - Diantika, Putu (JAPAM (Jurnal Pendidikan Agama), 2024)
Kramat Temple has beliefs that have multicultural nuances as seen from the worship carried out by two different religions, namely Hinduism and Islam. However, the positive construct of multicultural trust is not yet fully understood. Evidently, multicultural beliefs are only understood as unique things that occur in the area of ​​Hindu religious life. Narratively, this research tries to provide an exploration of positive reflection in a socio-religious frame that was born from the multicultural education frame at Kramat Temple. Data in this case was collected through observation techniques, interviews, document study, literature study, and discussed using the theory of multiculturalism. The results of this research show that the reflection of multicultural theology at Kramat Temple is as follows: first, multiculturalism education stimulates an increase in the quality of tolerance. Second, multicultural education has succeeded in strengthening universal brotherhood. Third, educational multiculturalism encourages valued attitudes. Fourth, multicultural education intensifies religious dialogue. True multicultural education cannot be done only by relying on theory and learning in formal schools. However, on the one hand, we need a real example, in this case the multicultural phenomenon at Kramat Temple